The latent structure of conative dimensions of elite senior and junior basketball players - Jakovljevic, S.; Karalejic, M.; Lazarevic, L. (Facta Universitatis: Series Physical Education and Sport, 2010)
The aim of the study was to investigate the conative dimensions of both senior and junior elite basketball players. In the sample of 80 senior and 80 junior basketball players, members of the best basketball senior and junior teams of Serbia, the following questionnaires related to the assessment of conative dimensions were administered: Cattell's 16 PF questionnaire (16 variables were obtained), Spielberg State Anxiety Trait - STAI (one variable was obtained), and the Havelka and Lazareviæ questionnaire of sports achievement- MSP (three variables were obtained). Standard descriptive statistics and factorial analysis, the main components method, were applied in data processing. In both groups of subjects, a latent structure of conative dimensions was expressed in seven factors, which in seniors encompass 64.594 % of the overall variance, and in juniors 67.672% of the overall variance. The factors were interpreted based on the highest projections of certain variables on the main components and based on the inspection of arithmetic means values. In the case of seniors, these factors can be interpreted as: orientation to achievement, extraversion, upbringing, emotional stability, self-reliance, imaginativeness and rationality. In the case of juniors the factors are interpreted as: emotional reactions, orientation to competition, sensitivity, reliance, apprehension, independence and orientation to achievement. The correlation between these factors within the latent structure of conative dimensions in both groups of subjects is not significant, meaning that these factors represent independent wholes.